2017
DOI: 10.4034/pboci.2017.171.46
|View full text |Cite
|
Sign up to set email alerts
|

Child’s Behavior and its Relationship with the Level of Maternal-Child Anxiety During Dental Care

Abstract: Objective: To evaluate the association between child's behavior and level of maternal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…However prevalence studies have shown that girls score higher on the CFSS-DS and they explained it on the fact that girls and younger children are more free in expressing and admitting their fears due to culture factors or associated stigmas [15,33]. On the other hand, some authors have reported a higher prevalence of dental fear among boys compared with girls [8,34].…”
Section: Discussionmentioning
confidence: 91%
“…However prevalence studies have shown that girls score higher on the CFSS-DS and they explained it on the fact that girls and younger children are more free in expressing and admitting their fears due to culture factors or associated stigmas [15,33]. On the other hand, some authors have reported a higher prevalence of dental fear among boys compared with girls [8,34].…”
Section: Discussionmentioning
confidence: 91%
“…There is a considerable interest on knowing the main aspects related to anxiety and fear in children and adolescents who, frequently, cannot clearly express what they feel on a frightening situation [3]. Several instruments have been developed and used to measure the anxiety of children and adolescents when facing the dental surgeon / pediatric dentist and in the dental environment, among which the Dental Anxiety Scale (DAS) [4], the facial image test (FIS) and the Venham Picture Test (VPT), developed in 1977 [6] and adapted to the Brazilian reality, entitled modified VPT [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated the level of anxiety in children and adolescents through the original version of the VPT test [8-11,]. However, there is lack in literature of studies that evaluate the modified VPT test in the Brazilian culture [1,2,3,[12][13][14]. There seems to be a gap in the evaluation of anxiety prior to dental treatment correlated with the age of patients, establishing comparatives in age groups in childhood and adolescence, especially among those who have had contact with the dental environment and those who have never had such experience [15].…”
Section: Introductionmentioning
confidence: 99%
“…The dental experience of many people is marked by technical-curative procedures that generate pain or discomfort, which leads to feelings of fear and anxiety, contributing to the maintenance of non-collaborative treatment standards [6][7][8][9][10][11][12][13]. Thus, the approach of the child patient becomes a challenge, leading to the development of appropriate reception and bond strategies, contextualized for the child's reality to enhance preventive action.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive procedures, such as anesthesia and tooth extraction, and dental instruments, such as syringe, carpule and high / low rotation motor, can generate negative emotions, including fear and anxiety. These emotions may lead to undesirable behavior patterns such as the unmarking of appointments and even denial of dental treatment[13,[21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%